Effect of N-methyl-D-aspartate on serum growth hormone level and pituitary growth hormone mRNA expression in finishing swine - MA Wen-qiang; FENG Jie; XU Zi-rong (浙江大学学报. 农业与生命科学版)
Sixty crossbred (Duroc× Landrace× Yorkshire) finishing pigs were used to study the effects of N-methyl-D-aspartate (NMDA) on serum growth hormone (GH) level and pituitary GH mRNA expression. Pigs weighed averagely about 60 kg were randomly allotted to two treatments and fed diets containing 0 and 100 mg·kg-1 NMDA respectively for 43 days. At the end of the experiment, six pigs of each treatment were slaughtered humanly to collect the serum and pituitary samples. The experimental results show that NMDA increased serum GH concentrations in barrows and gilts by 36.91% and 45.95% (P<0.05), respectively. It was also found that NMDA enhanced the GH mRNA level by 48.75% (P<0.05) compared with control. The results above indicate manipulation on GH secretion maybe one of the main reasons for NMDA affecting the growth performance of finishing swine.